His majesty, the rocoto pepper - Blanco de Alvarado-Ortiz, Teresa (2016)
The demand for food and agricultural products is undergoing unprecedented change. Income growth, urbanization and the entrance of women into the job market have led to population growth and increased needs for highly nutritious, processed and prepared foods. Meanwhile, commerce, communications and tourism have been accelerating the shift to healthy eating patterns and a growing interest in native foods. The nature and scope of the versatile structure of this demand for agro-food offers exceptional opportunities for diversification and value-added in the agricultural industry, particularly in the developing countries